Internal laryngocoele and referred otalgia. (26th November 2010) - Vedasalam, S; Sipaul, F; Porter, G
Abstract : A 74-year-old woman presented with severe right ear pain associated with bleeding of 2 months' duration and vertigo. She was otherwise fit and well apart from arthritis. On examination there was dried blood overlying the right ear drum and very mild inflammation of the canal but no obvious acute infection. The dried blood was removed in subsequent clinic visits. The ear drum was intact and there was no evidence of infection. However, the patient still had persistent pain in the right ear. A diagnosis of referred otalgia was made. Nose, throat, neck, temporo-mandibular joint, oral examination and flexible nasoendoscopic examination were normal. She underwent MRI of her neck which revealed a right supraglottic mass. Laryngoscopy was performed. Intra-operative findings revealed a smooth right supraglottic mass, which was thought to be an internal laryngocoele. The laryngocoele was de-roofed. The histology specimen showed no evidence of neoplasia.